Does Cognition Still Matter in Ethnobiology? - David Ludwig (Ethnobiology Letters, 2018)
Ethnobiology has become increasingly concerned with applied and normative questions about biocultural diversity and the livelihoods of local communities. While this development has created new opportunities for connecting ethnobiological research with ecological and social sciences, it also raises questions about the role of cognitive perspectives in current ethnobiology. In fact, there are clear signs of institutional separation as research on folkbiological cognition has increasingly found its home in the cognitive science community, weakening its ties to institutionalized ethnobiology. Rather than accepting this separation as inevitable disciplinary specialization, this short perspective article argues for a systemic perspective that addresses mutual influences and causal entanglement of cognitive and non-cognitive factors in socio-ecological dynamics. Such an integrative perspective requires a new conversation about cognition in ethnobiology beyond traditional polarization around issues of cognitive universals and cultural relativity.